2013
DOI: 10.1007/s11481-013-9493-1
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Decrease the Th17 Inflammatory Autoimmune Phenotype

Abstract: Cannabinoids, the Cannabis constituents, are known to possess anti-inflammatory properties but the mechanisms involved are not understood. Here we show that the main psychoactive cannabinoid, Δ-9-tetrahydrocannabinol (THC), and the main nonpsychoactive cannabinoid, cannabidiol (CBD), markedly reduce the Th17 phenotype which is known to be increased in inflammatory autoimmune pathologies such as Multiple Sclerosis. We found that reactivation by MOG35-55 of MOG35-55-specific encephalitogenic T cells (cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 68 publications
8
91
2
Order By: Relevance
“…A recent study showed that THC reduces Th17 (49). However, in this study, these histone methylation markers were not associated with Rorc, which regulates Th17 (data not shown).…”
Section: Histone Methylation Pattern and Gene Expression-becausecontrasting
confidence: 80%
“…A recent study showed that THC reduces Th17 (49). However, in this study, these histone methylation markers were not associated with Rorc, which regulates Th17 (data not shown).…”
Section: Histone Methylation Pattern and Gene Expression-becausecontrasting
confidence: 80%
“…In addition, serum levels of IFN-γ, IL-10, IL-12, or C-reactive protein in MS patients have not been reported to have any influence on the development of the disease [85]. Nevertheless, a study by Arevalo-Martin et al [86] The potential use of cannabinoids in the treatment of MS also involves the reduced synthesis and secretion of IL-17 by THC and CBD, thereby suppressing the Th17 response [87] which is commonly increased in patients with inflammatory autoimmune pathologies such as MS [88].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…This raises questions about whether cannabis might be associated with behaviors that are linked to lower rates of obesity, such as physical activity. Some studies have suggested that cannabinoids may exert positive effects on health by decreasing inflammation and decreasing pain [5], and it is possible that such properties might have implications for recovery from exercise. There are also anecdotal reports that cannabis is used prior to athletic activity to enhance performance.…”
Section: Introductionmentioning
confidence: 99%